Association of Postoperative Dieting, Exercise, Dietitian, and Surgeon Follow up With Bariatric Surgery Outcomes. Issue 10 (October 2022) - Samaan, Jamil S.; Srinivasan, Nitin; Mirocha, James; Premkumar, Agnes; Toubat, Omar; Qian, Elaine; Subramanyam, Chaitra; Malik, Yousaf; Lee, Nayun; Sandhu, Kulmeet; Dobrowolsky, Adrian; Samakar, Kamran
Although postoperative diet modification, exercise, and regular dietitian and surgeon follow-up are often recommended after bariatric surgery (BS), their impact on weight loss is unclear. A Retrospective chart review was conducted for patients who received sleeve gastrectomy or Roux-en-Y gastric bypass (RYGB) between August 2000 and November 2017 with telephone follow-up. Multivariable logistic regression models were used for analyses. There were 514 patients included in our study. Most were female (76.3%), mean age was 46.9 years (Standard Deviation [SD] = 11.8), and mean weight loss was 11.6 (SD = 6.5) BMI points at a mean follow-up of 7 years (SD = 4.3). Current surgeon follow-up OR = 2.08 (P < .01) was positively associated with postoperative weight loss, while current dietitian follow-up=OR .41 (P < .01) was negatively associated. Current weight loss supplement use OR = .45 (P = .03) was associated with reduced willingness to undergo surgery again. Increasing preoperative BMI OR = 1.06 (P = .04) and increasing age OR = 1.04 (P = .02) were associated with improved quality of life (QoL) due to BS. Lack of surgeon follow-up and regular dietician consultation was associated with suboptimal weight loss after BS. Older age was positively associated with improved QoL, while current weight loss supplement use was associated with lower likelihood of undergoing surgery again, both independent of weight loss.